Perancangan Cafe-Library and Resto di Surabaya - Richmond Shan Chandra; martino dwi nugroho; Grace Mulyono (Intra, 2015)
The design of Cafe-Library and Resto is one of the new breakthrough in creating a new ambience in a library and giving it a unique atmosphere and can attract people’s interests. Besides, development of the culinary world has expanded rapidly, whereas people often spend their time to visit a restaurant or café to relax or to do something. Usually, restaurant and café business find it hard to decide the loyalty of a customer, because the customer always want to try and enjoy a new menu and ambience as well. Only a few people who are truly loyal to a restaurant or café. Which brings us to the development of restaurants in indonesia that are focussing to the young customer’s segmentation that always want to try new things and making them not only just a satisfy the hunger, but also a place to gather with friends and families. By creating a new ambience such as the Cafe-Library and Resto design, the customers can enjoy a restaurant-class dish and also read or look for some information at the mini library. Supported by a commercial interior design, it is expected from this design to increase people’s interest to visit this place. So, this Cafe-Library and Resto design can accommodate people’s activities and is compatible with those standards of comfort, safety, and also customer’s need and fullfill its purpose.